2007
DOI: 10.1111/j.1600-0838.2007.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year comparison of anterior cruciate ligament reconstructions with hamstring tendon and patellar tendon autograft: a controlled, prospective trial

Abstract: BACKGROUND: There are no controlled, prospective studies comparing the 10-year outcomes of anterior cruciate ligament (ACL) reconstruction using patellar tendon (PT) and four-strand hamstring tendon (HT) autografts. HYPOTHE-SIS: Comparable results are possible with HT and PT autografts. STUDY DE-SIGN: Cohort study; Level of evidence, 2. METHODS: One hundred and eighty ACL-deficient knees that met inclusion criteria underwent ACL reconstruction (90 HT autograft, 90 PT autograft) by one surgeon and were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
318
3
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(346 citation statements)
references
References 0 publications
18
318
3
7
Order By: Relevance
“…This finding may point to the fact that the YBT-LQ is a trainable skill in which quadriceps strength plays a role in improvements following ACL-R, in addition to neuromuscular control, hip strength and range of motion of the entire lower extremity. Garrison et al 24 found that gluteal strengthening contributes to YBT-LQ ANT. Individuals that scored higher on the YBT-LQ at 12-weeks, but had decreased quadriceps strength may have had an increase in gluteal strength between the preoperative assessment and assessment at 12-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may point to the fact that the YBT-LQ is a trainable skill in which quadriceps strength plays a role in improvements following ACL-R, in addition to neuromuscular control, hip strength and range of motion of the entire lower extremity. Garrison et al 24 found that gluteal strengthening contributes to YBT-LQ ANT. Individuals that scored higher on the YBT-LQ at 12-weeks, but had decreased quadriceps strength may have had an increase in gluteal strength between the preoperative assessment and assessment at 12-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for the development of knee OA after ACL injury are reported in the literature [75,41,84,85,24]. A systematic review discussed whether the risk of developing knee OA might be somewhat exaggerated in the literature [64].…”
Section: A Successful Return To Sportsmentioning
confidence: 99%
“…Strong evidence identifying meniscal injury and meniscectomy as risk factors for 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 the development of knee OA after ACL injury was found [64]. However, the results in a single-leg hop test one year after the ACL injury have been stated as a predictor of future development of knee OA [75] and muscle weakness is commonly suggested to be a risk factor [24]. It has further been suggested that neuromuscular function may be of importance in preventing knee OA [81,100,71,40] and that poor muscle function might be a predictor of OA development [92,93,75].…”
Section: A Successful Return To Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these standard objective measures such as these are temporal based measures and therefore are quit variable and may have limitations if used in isolation to determine return to full activity. This is concerning since as many as one in four patients undergoing an ACL reconstruction will suffer a second tear within 10 years of their first [101]. Furthermore recent biomechanical data has shown that altered neuromuscular control of the hip and knee during a dynamic landing task as well as postural stability deficits after ACL reconstruction are predictors of a second ACL injury after an athlete has returned to sports [102•].…”
Section: Phase Iv: Postoperative 3 Months-6 Monthsmentioning
confidence: 99%